THE TRANSFORMATION OF ISLAMIC EDUCATIONAL DA’WAH IN CONFRONTING WESTERN HEGEMONY: THE THOUGHT OF MUHAMMAD ABDUH, AL-AFGHANI, AND THE RESPONSES OF MUHAMMADIYAH AND NAHDLATUL ULAMA - Selvi Syahfitri; Tatu Nurkamilah; Rifqi Amrulloh; Amelia Fauzia; Iin Kandedes (J-MD Jurnal Manajemen Dakwah, 2026)
This study examines the reform of modern Islamic education within the context of Western hegemony through the educational thought of Muhammad Abduh and Jamal al-Din al-Afghani, as well as the responses of Muhammadiyah and Nahdlatul Ulama toward colonial education in Indonesia. The nineteenth century marked a period of multidimensional crisis in the Muslim world due to political decline, intellectual stagnation, and the expansion of Western colonialism, which introduced not only political domination but also epistemological hegemony through modern secular education systems. In this context, Islamic reformist thinkers emerged to reconstruct Islamic educational thought as a strategy for civilizational revival. This research employs a qualitative approach using library research methods with historical and philosophical perspectives. Primary data were obtained from the works and ideas of Al-Afghani and Abduh, while secondary data were collected from reputable national and international academic journals, books, and historical studies related to Islamic educational reform and colonialism. Data were analyzed using content analysis and critical-interpretative approaches to identify the relationship between Islamic educational reform and resistance to Western epistemological domination. The findings reveal that Al-Afghani emphasized Pan-Islamism, political consciousness, and scientific advancement as instruments for resisting Western imperialism, whereas Abduh focused on educational modernization through the integration of reason and revelation, curriculum reform, and the revitalization of Islamic intellectual traditions. Furthermore, the study demonstrates that Muhammadiyah and Nahdlatul Ulama adapted these reformist ideas differently according to the Indonesian socio-cultural context. Muhammadiyah adopted a modernist educational model integrating religious and general sciences through modern schools, while Nahdlatul Ulama maintained pesantren traditions through adaptive traditionalism and selective modernization. The study concludes that Islamic educational reform in Indonesia represents not a process of Westernization, but rather an epistemological negotiation aimed at preserving Islamic identity while engaging with modern global civilization.